Design, Fabrication and Validation of Thin Bamboo Slicing Machine for Bamboo Fiber Processing - SHAHRI, SYAZLIN NATASYA SURAYA BINTI SHAHRI (Progress in Engineering Application and Technology, 2023)
Bamboo is a highly renewable and sustainable resource that has a wide range of uses in construction, textiles, pulp and paper, food, medicine, furniture and landscaping. However, the traditional manual methods of bamboo slicing are time-consuming and labor-intensive.This is because the process typically involves cutting the bamboo by hand using a machete or other cutting tool. This can be a slow and physically demanding process, especially for large quantities of bamboo.To address this issue, a bamboo slicing machine was designed and fabricated to automate the process of bamboo slicing. The machine consists of a feeding mechanism and slicing mechanism. The feeding mechanism is used to align the bamboo before slicing, while the slicing mechanism uses a blade to slice the bamboo into the desired thickness. Through detailed research, analysis, and experimentation, a functional prototype of the machine was developed. The results of this research demonstrate the feasibility and practicality of using this machine in real-world applications. The fabrication of this bamboo slicing machine can greatly improve the efficiency and accuracy of bamboo slicing, reducing labor costs and increasing production capacity.